Alternative solution for pre-treatment of seawater for the desalination process - Goh, Qing Kai (Nanyang Technological University, 2021)
The applicability of novel low pressure nanofiltration (NF) membrane as a pre-treatment stage prior to reverse osmosis (RO) process for desalination of seawater was investigated in a laboratory-scale study. The performance of NF membrane and resultant permeate quality was tested and compared with that of ultrafiltration (UF) membrane. Salt rejection, total organic compounds (TOCs) rejection and overall flux performance of the NF and UF membranes using seawater as feed served as the basis of comparison for this study. Experiments conducted showed that the rejection of both salt and TOCs of NF membranes were much better than the UF membranes and displayed better flux performance during a continuous operation using seawater as feed. The average salt rejection of NF membrane was 3.99% at 2.5 bar while that of UF membrane was only at 0.42%. Additionally, at the same respective operating pressure, the NF membrane showed higher TOC rejection of 69.4% to that of UF membrane which was only 14.9%. The NF membranes were able to sustain its original flux performance at 2.5 bar much longer than the UF membrane could at 0.25 bar. Following that, collection of NF permeate was done continuously from the NF membrane, with seawater as feed. Subsequently, the NF permeate was fed into a closed-loop seawater reverse osmosis (SWRO) process, with resultant RO permeate compared to the quality of permeate of an integrated UF + RO system that was collected in previous study. Lastly, various membrane cleaning methods were also evaluated to determine which of the tested methods showed highest flux recovery in the NF membrane. From the tests conducted, it was concluded that backwashing with sodium hydroxide showed the highest flux recovery.